ANALYSIS OF SOIL BEARING CAPACITY AND FOUNDATION SETTLEMENT IN THE CONSTRUCTION OF GUPUSMU PUSPALAD III JAKARTA - Anasya Arsita Laksmi; Arya Maulana Kampai; Harjasa Jonathan; Nina Purwanti; Deakonius Silalahi; Dewa Ramadhan Astama Putra; Dewi Fauzah; Abdul Hadi Adriansyah; Abigail Christy; Andreas Robert Panogu Sitorus; Sigit Adi Soebekti (Jurnal Ilmiah Teknik Sipil, 2024)
The ammunition center warehouse and military equipment center are strategically important for Army operations. In the design, an analysis of soil bearing capacity and foundation settlement is required to maximize the structural load of the ammunition center building. Based on this, this study aims to analyze the soil-bearing capacity and potential deformation of the foundation in response to the structural loads applied to the construction of the Ammunition Center Warehouse and Army Equipment Center III in Jakarta. The investigation involved six lightweight sondir points, each with a capacity of 2.5 tons, to obtain a conus value of 250 kg/cm2. The information obtained from the sondir test was used to determine the bearing capacity of the soil and the amount of foundation settlement that might occur. Based on the analysis and calculations, a shallow foundation, namely a 2-meter-deep footing, was selected. The allowable soil bearing capacity is 1.18 kg/cm2, and the foundation settlement at P1 is about 2.8 cm and 1.3 cm at P2. This research is expected to be the basis for designing ammunition warehouse foundations in military institutions.